CHRONIC SINUSITIS: PATHOPHYSIOLOGY, DIAGNOSIS, AND MANAGEMENT (E Global Congress, 2025)
Chronic sinusitis, also known as chronic rhinosinusitis (CRS), is a prolonged inflammatory condition affecting the paranasal sinuses and nasal passages lasting more than 12 weeks. Unlike acute sinusitis, which is commonly infectious in origin, chronic sinusitis is characterized by persistent mucosal inflammation that may or may not be associated with infection. CRS significantly affects patients' quality of life, with symptoms including nasal obstruction, facial pain, postnasal drip, and hyposmia. This article reviews the pathophysiology, clinical presentation, diagnostic approaches, and evidence-based treatment options for chronic sinusitis, with emphasis on the importance of multidisciplinary care and individualized management strategies.